Practicing Social Cohesion in the Dark: Diverse Processes and Missing Indicators in Forced Migration Contexts - Ozcurumez, Saime; Hoxha, Julinda (Frontiers in Human Dynamics, 2020)
Despite the large number of studies on social cohesion, research carried out in non-European, refugee and local contexts remains limited. This article provides a structured, focused comparison of social cohesion practices in new refugee hosting settings based on examples from Turkey, Lebanon, and Jordan. The analysis reveals that social cohesion vision is implemented through peacebuilding, community engagement, and resilience building practices that aim at building safe, shared and empowered spaces respectively. In contrast to national policies with more immediate, tangible and standardized outcomes, local practices involve intercommunal, interactional, and future-oriented processes, which complicates the assessment of social cohesion through an indicator framework. Based on the findings, the article suggests (a) acknowledging context bound manifestations of social cohesion practices, (b) emphasizing social interactions at the local level as a crucial component of social cohesion processes, and (c) advancing research on the causal mechanisms of social cohesion as a long-term policy goal.